Clinical implementation of MR‐guided vaginal cylinder brachytherapy - Owrangi, Amir M. (J Appl Clin Med Phys, 2015)
We present an institutional experience on the clinical implementation of magnetic resonance (MR)‐guided vaginal brachytherapy using commercially available solid applicator models. To test the fidelity of solid applicator models to digitize vaginal cylinder applicators, three datasets were evaluated. The first included 15 patients who were simulated with CT alone. Next, a water phantom was used to evaluate vaginal cylinders ranging from 20 to 35 mm in diameter with CT and MR. Finally, three patients undergoing HDR brachytherapy with vaginal cylinders that were simulated with both CT and MR were evaluated. In these assessments, the solid applicator models were aligned based on the outline of the applicators on the corresponding volumetric image, and deviations between the central source positions defined based on X‐ray markers (on CT) and solid applicator models (on CT and MR), and the percent dose difference between select reference points were calculated. The mean central source deviation defined based on X‐ray markers (on CT) and solid applicator models (on CT and MR) for the 15‐patient cohort, the phantom, and the 3‐patient cohort is 0.6 mm, 0.6 mm, and 1.2 mm, respectively. The average absolute percent dose difference for the bladder, rectum, prescription, and inferior reference points were 2.2%, 2.3%, 2.2%, and 2.4%, respectively, for the 15 patient cohort. For the phantom study, the average, absolute percent dose difference for the prescription and inferior reference points are 2.0% and 2.1% for the CT, 2.3% and 2.2% for the T1W, and 2.8% and 3.0% for the T2W images. For the three patient cohort, the average absolute percent dose difference for the bladder, rectum, prescription, and inferior reference points are 2.9%, 2.6%, 3.0%, and 4.2% for the CT, 6.5%, 1.6%, 2.5%, and 4.7% for the T1W, and 6.0%, 7.4%, 2.6, and 2.0% for the T2W images. Based on the current study, aligning the applicator model to MR images provides a practical, efficient approach to perform MR‐based brachytherapy planning. PACS numbers: 87.53.Jw, 87.61.Tg